Calcium silicate-based cements associated with micro-and nanoparticle radiopacifiers: physicochemical properties and bioactivity - Bosso-Martelo, Roberta [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Viapiana, Raqueli [UNESP]; Berbert, Fábio Luis Camargo Vilella [UNESP]; Basso Bernardi, Maria Inês; Tanomaru Filho, Mario [UNESP] (Hindawi, 2015)
The aim of this study was to evaluate the physicochemical properties and bioactivity of two formulations of calcium silicate-based cements containing additives (CSCM) or resin (CSCR), associated with radiopacifying agents zirconium oxide (ZrO2) and niobium oxide (Nb2O5) as micro- and nanoparticles; calcium tungstate (CaWO4); and bismuth oxide (Bi2O3). MTA Angelus was used as control. Methods. Surface features and bioactivity were evaluated by scanning electron microscopy and the chemical composition by energy dispersive X-ray spectrometry (EDS-X). Results. CSCM and CSCR presented larger particle sizes than MTA. Hydroxyapatite deposits were found on the surface of some materials, especially when associated with the radiopacifier with ZrO2 nanoparticles. All the cements presented calcium, silicon, and aluminum in their composition. Conclusion. Both calcium silicate-based cements presented composition and bioactivity similar to MTA when associated with the radiopacifiers evaluated.
Keywords: Mineral trioxide aggregate; Radiopacity; Physicochemical properties